The Right Look: Conservative Politicians Look Better and Voters Reward It - Niclas Berggren; Henrik Jordahl; Panu Poutvaara (Research Institute of Industrial Economics (IFN), 2010)
Political candidates on the right are more beautiful or are seen as more competent than candidates on the left in Australia, Finland, France, and the United States. This appearance gap gives candidates on the right an advantage in elections, which could in turn influence policy outcomes. As an illustration, the Republican share of seats increased by an average of 6% in the 20002006 U.S. Senate elections because they fielded candidates who looked more competent. These shifts are big enough to have given the Republicans a Senate majority in two of the four Congresses in the studied time period. The Republicans also won nine of the 15 gubernatorial elections where looks were decisive. Using Finnish data, we also show that beauty is an asset for political candidates in intra-party competition and more so for candidates on the right in low-information elections. Our analysis indicates that this advantage arises since voters use good looks as a cue for conservatism when candidates are relatively unknown.
Keywords: D72; J45; J70; 330; Beauty; Elections; Political candidates; Appearance; Ideology; Parties; Wahlkampf; Politiker; Wahlverhalten; Ideologie; Neue politische Ökonomie; Finnland